ANÁLISE MORFOFUNCIONAL MUSCULAR PERIFÉRICA ULTRASSONOGRÁFICA EM PACIENTES NEUROCRÍTICOS: DA ADMISSÃO À ALTA HOSPITALAR - Talita Santos de Arruda (2025)
Introduction: Acute brain injury can result in deficits in cognitive and emotional function, as well as motor sequelae. Early evaluation and quantification of muscle loss is a challenge in the context of non-collaborative patients. Objective: To analyze the relationship between peripheral muscle characteristics, through ultrasonography (USG), and clinical and functional outcomes in neurocritical patients from admission to hospital discharge. Method: This is a longitudinal, observational, and descriptive study conducted on neurocritical patients admitted to a Neurological ICU. Patients with severe acute brain injury of traumatic or vascular origin, within 48 hours of admission, were included. Muscle USG was performed at three time points: at admission, at ICU discharge, and at hospital discharge, assessing the muscle thickness and cross-sectional area of the biceps brachii, quadriceps femoris, and rectus femoris muscles, as well as the echogenicity of the rectus femoris muscle. Additionally, functionality was assessed using the IMS mobility scale. At the final hospital discharge assessment, patients were divided into groups with and without motor sequelae. Results: The final sample included 43 patients. In the overall sample, there was a significant reduction in the muscle thickness of the bilateral biceps brachii (p < 0.0001), bilateral quadriceps (p < 0.0001), and the cross-sectional area of the bilateral rectus femoris (p < 0.0001). The echogenicity of the left rectus femoris also showed a significant reduction (p < 0.0001). Age showed a strong negative correlation with the muscle thickness of the right rectus femoris (r = -0.751) and the right cross-sectional area (r = -0.727), as well as a moderate correlation with the muscle thickness of the right (r = -0.643) and left quadriceps (r = -0.647), left rectus femoris (r = -0.674), and with the left cross-sectional area (r = -0.70). A strong positive correlation was also observed between the ICU length of stay and mechanical ventilation use (r = 0.825), as well as a moderate correlation between hospital length of stay and ICU length of stay (r = 0.599). Functionality showed a moderate negative correlation with age (r = -0.635). Conclusion: Peripheral muscle loss in neurocritical patients had a significant impact on functionality, particularly in patients with sequelae. Ultrasonographic analysis revealed significant reductions in muscle thickness and cross-sectional area of the biceps brachii, quadriceps, and rectus femoris between admission and hospital discharge. The correlation between clinical and ultrasonographic variables showed significant associations between muscle characteristics, age, length of stay, and functionality.